Competencies for rehabilitation professionals working with ideology-based terrorism offenders - Sukabdi, Zora A. (Crime, law and social change, 2022)
Selection of competent personnel is critical to in terrorism rehabilitation efforts. Elucidating the characteristics of effective rehabilitation staff and determining personal and professional competencies has however been neglected. This study seeks to systematically identify competencies needed for staffs working with terrorism offenders in Indonesia. Semi-structured interviews with Indonesian counterterrorism experts, practitioners, and professionals were conducted and data were analysed using qualitative and quantitative methods. Findings suggest four general/core and forty specific competencies are helpful for rehabilitation therapists and other staff working with ideology-based terrorist offenders. The findings may be used by service providers responsible for the design and implementation of deradicalization and terrorism offender rehabilitation.